STRUKTUR KEPRIBADIAN MENURUT IBN MISKAWAIH DAN IMPLIKASINYA PADA LAYANAN KONSELING DAN TERAPI ISLAMI - Alfin Siregar (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
This paper aims to explore the Muslim philosopher (Ibn Miskawayh) about the structure of human personality that implies the activities of Islamic counseling services. During this time, counseling practice is still based on the paradigm of western thinkers in looking at the structure of human personality. In fact, many Muslim figures such as Ibn Miskawayh have devoted their thoughts to aspects of human life. Ibn Miskawayh argues that human personality is based on three aspects: Nafs Natiqah, Nafs Al Sibaiyyah, and Nafs Al Hayawaniyyah. According to him also, the three driving forces of such behavior, has a tendency to dominate one another. Therefore, the offer proposed by Ibn Miskawayh is the emergence of the balance of the driving force of behavior, through several models of therapy and counseling services in an Islamic model.Keyword: Ibn Misakawaih, structure of Personality, Islamic models couseling/therapies.